2014
DOI: 10.4314/njp.v41i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of children and adolescents with thyroid disorders seen at the University of Port Harcourt Teaching Hospital: A five year review

Abstract: BackgroundThyroid disorders constitute a large proportion of endocrine diseases in children and adolescents. Diseases of the thyroid have profound effect on metabolism, cognition, growth and development in children. The pattern of thyroid disorders in children in our region is still under reported. Objectives: To describe the clinical characteristics of children and adolescents with thyroid diseases seen over a 5 year period in a tertiary centre in Port Harcourt Methods: A retrospective review of all cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 9 publications
4
17
2
Order By: Relevance
“…No child with hypothyroidism has been identified with this programme thus far. However, there are reports of CH in babies born within the study period in one of the included cities [12] but not in the collaborating hospitals. This highlights the need to improve the scale-up in all hospitals and to make the programme national rather than institutional as it is at the present time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No child with hypothyroidism has been identified with this programme thus far. However, there are reports of CH in babies born within the study period in one of the included cities [12] but not in the collaborating hospitals. This highlights the need to improve the scale-up in all hospitals and to make the programme national rather than institutional as it is at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…There is also no known nationwide study on the problem of CH in Nigeria. However, there are several studies [9,10,11,12] that have reported cases of CH in Nigerian children. For proper and evidence-based advocacy, there is a need to determine the prevalence of CH in the Nigerian population.…”
Section: Introductionmentioning
confidence: 99%
“…This rate is, however, higher than the incidence of 0.07% reported in a previous Nigerian study by Laditan and Johnson 4 in Ibadan, South-West Nigeria, done about 40 years ago. The higher incidence rates of the index study and other relatively recent studies 6 7 may be related to more awareness about pediatric endocrine diseases in the country due to the development of the subspecialty in Nigeria and training of more medical personnel. With regard to the extent endocrine diseases contribute to the burden of pediatric consultations, the percentage of 1.03% in the present study is slightly higher than the rates of 0.72% in Benin and 0.2% in Ibadan, both in Nigeria,.…”
Section: Discussionmentioning
confidence: 80%
“…This is comparable to the rates of 0.12% and 0.1% documented in recent reports by Onyiriuka et al . 6 and Jaja and Yarhere 7 from Benin and Port Harcourt, both in South-South Nigeria, respectively. This rate is, however, higher than the incidence of 0.07% reported in a previous Nigerian study by Laditan and Johnson 4 in Ibadan, South-West Nigeria, done about 40 years ago.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation